Rapid detection method of bacteria species on diabetic infected foot using E-Nose technology - Muhammad Nur Hadi, Salleh; Mohammad Iqbal, Omar, Assoc. Prof. Dr.; Ali Yeon, Md. Shakaff, Prof. Dr.; Amizah, Othman, Dr.; Ammar, Zakaria; Azian Azamimi, Abdullah; Mohd Sadek, Yasin; Saiful Akmal, Yusof (Macao Innovation & Invention Association, 2013)
The team has won bronze medal at Macau International Innovation & Invention Expo 2012, 29th June - 1st July 2012 was held at Macau Fisherman Wharf Exhibition Centre Macau, China.